Jasmonic Acid-Mediated Aliphatic Glucosinolate Metabolism Is Involved in Clubroot Disease Development in Brassica napus L. - Xu, Li; Yang, Huan; Ren, Li; Chen, Wang; Liu, Lijiang; Liu, Fan; Zeng, Lingyi; Yan, Ruibin; Chen, Kunrong; Fang, Xiaoping (Frontiers in Plant Science, 2018)
Glucosinolate (GSL) is associated with clubroot disease, which is caused by the obligate biotrophic protist Plasmodiophora brassicae. Due to the complicated composition of GSLs, their exact role in clubroot disease development remains unclear. By investigating clubroot disease resistance in Cruciferous plants and characterizing the GSL content in seeds, we can determine if clubroot disease development is related to the components of GSLs. The difference in the infection process between Matthiola incana L. (resistant) and Brassica napus L. (susceptible) was determined. Root hair infection was definitely observed in both resistant and susceptible hosts, but no infection was observed during the cortical infection stage in resistant roots; this finding was verified by molecular detection of P. brassicae via PCR amplification at various times after inoculation. Based on the time course detection of the contents and compositions of GSLs after P. brassicae inoculation, susceptible roots exhibited increased accumulation of aliphatic, indolic and aromatic GSLs in B. napus, but only aromatic GSLs were significantly increased in M. incana. Gluconapin, which was the main aliphatic GSL in B. napus and present only in B. napus, was significantly increased during the secondary infection stage. Quantification of the internal jasmonic acid (JA) concentration showed that both resistant and susceptible plants exhibited an enhanced level of JA, particularly in susceptible roots. The exogenous JA treatment induced aliphatic GSLs in B. napus and aromatic GSLs in M. incana. JA-induced aromatic GSLs may be involved in the defense against P. brassicae, whereas aliphatic GSLs induced by JA in B. napus likely play a role during the secondary infection stage. Three candidate MYB28 genes regulate the content of aliphatic GSLs identified in B. napus; one such gene was BnMYB28.1, which was significantly increased following both the treatment with exogenous JA and P. brassicae inoculation. In summary, the increased content of JA during the secondary infection stage may induce the expression of BnMYB28.1, which caused the accumulation of aliphatic GSLs in clubroot disease development.